Directory of NGOs for migrants in Asia. - Scalabrini Migration Center (Quezon City Scalabrini Migration Center, 1994)
An initial, limited attempts to facilitate networking among organizations involved in assisting migrants in different countries. The directory is of composite nature, it comprises of NGOs, migrant associations, and sometimes affiliates of international organizations. The 147 organizations are arranged alphabetically by country and include information such as address, telephone numbers, contact persons, year founded, number of staff, number of members, group served, purpose, service, major activities, publications, language, and networking associations. The directory also feature an index of service where the organizations are listed according to the services they provide.
"This directory is an initial, limited attempt to facilitate networking. It is the result of contacts with NGOs, particularly in East Asia, to which questionnaire was submitted. For those who answered, the directory provides a complete profile as furnished by them. However, those organizations which did not return the questionnaire are listed in appendix. NGOs are listed by country, and in alphabetical order within the country. An index to the services provided by NGOs is also included."
Keywords: Alien labor, Asian -- Directories; Non-governmental organizations -- Asia -- Directories; Asia -- Emigration and immigration -- Directories